Perancangan User Interface Aplikasi PMKS Pendataan Anak Yatim Dengan Metode HCD - Pratama, Gilang; Zulkarnaen, Muhammad Fauzi (Jurnal Ilmiah IKIP Mataram, 2023)
This study aims to design an optimal user interface for the PMKS (Social Welfare for the Disabled) website for orphan data collection in Central Lombok, using the Human-Centered Design (HCD) approach. The research encompasses the stages of user needs analysis, user interface design, and user interface evaluation.In the user needs analysis stage, data is gathered through observation, interviews, and competitor analysis. The findings are used as a reference for designing an improved user interface. The user interface design stage involves utilizing the collected data to develop an initial prototype tailored to the users’ needs and characteristics. The prototype is then tested through usability testing to ensure that the user interface design meets the users’ needs and expectations.The user interface evaluation stage is conducted to assess the effectiveness and efficiency of the developed design. Feedback is collected from users through interviews, surveys, and observations to refine the user interface design according to user requirements. The evaluation results serve as feedback for the developers to improve the user interface design.By implementing the HCD approach in designing the user interface for the PMKS orphan data collection website in Central Lombok, it is expected to enhance the user experience, improve the efficiency of orphan data collection, and facilitate the tasks of PMKS staff involved in orphan data management. This research contributes to the development of a better and reliable orphan data management system in PMKS Central Lombok.